Human Capital Specificity: Evidence from the Dictionary of Occupational Titles and Displaced Worker Surveys, 1984–2000 - Poletaev, Maxim; Robinson, Chris (Journal of Labor Economics, 2008)
Measures of four basic skills, constructed from the Dictionary of Occupational Titles, are used to examine the source of human capital specificity. The measures are used to characterize the skill portfolio of each job and to construct distance measures between jobs. Wage losses in the Displaced Worker Surveys are shown to be more closely associated with switching skill portfolios than switching industry or occupation code per se. These switches represent large decreases in the skill portfolio in the postdisplacement job. The recent evidence for industry‐specific capital is reexamined. The results suggest a difference between fluid and crystallized skills.